Factors Impacting the Behavioural Intention to Use E- learning at Higher Education amid the Covid-19 Pandemic: UTAUT2 Model - Raman A; Thannimalai R (Moscow State University of Psychology and Education, 2021)
The purpose of this study is to evaluate the behavioral intention of higher education students to use e-learning during the Covid-19 pandemic. Not many re- searchers have utilized the UTAUT2 model to study the use of technology during this pandemic in the education setting. Therefore, snowball sampling was carried out and the research population consisted of higher education students (n = 159) who have been using e-learning platforms during the ongoing pandemic. The data was collected using a questionnaire based on the adapted UTAUT2 model. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was used for statistical analysis. Social Influence and Habit significantly influenced Behavioral Intention to use e-learning. However, Performance Expectancy, Effort Expectancy, Facilitating Conditions, Hedonic Motivation and Price Value did not have any influence. Habit was found to be the strongest predictor for Behavioral Intention. The findings of this study will guide higher educations to consider the factors for effective implementation of e-learning in an academic setting and provide directions for future research.